Effect of Metal Oxides Nanoparticles on the Optical Properties of Poly(vinyl chloride)/Poly(vinylidene fluoride) Blends Electrolytes Plasticized with Glycerol - Hasson, Russul Alaa; Hasan, Ahmad Abbas (Iraqi Journal of Physics, 2024)
Lithium-ion batteries (LIBs) are beginning to use solid polymer electrolytes (SPEs) as a potentially useful replacement for liquid electrolytes. However, incompatibility between the lithium metal anode and electrolyte, which results in low ionic conductivity and reduced cycling performance of LIBs, is one of the disadvantages of SPEs. Solution casting with glycerol as a plasticizer was used to create electrolyte films consisting of 80% Poly (vinylidene fluoride) (PVDF) and 20% poly (vinyl chloride) (PVC), undoped and doped with various salts, including lithium carbonate (Li2CO3) and lithium chloride (LiCl) and various metal oxides (CuO, WO3, and TiO2) nanoparticles (NPs). An investigation was conducted to examine their impact on optical properties. The prepared SPEs were characterized by UV-visible and Fourier transformer infrared spectroscopy (FTIR). The results showed that the type of salt and doping greatly affected the energy gap. The energy showed a blue shift after the addition of lithium carbonate, while it showed a red shift after doping with metal oxides (WO3 and TiO2) NPs; the minimum energy gap was 1.6 eV obtained from SPE (PVC/PVDF/Li2CO3) doped with TiO2 NPs, while the energy gap showed red shift after adding LiCl. It changed non-regularly after doping with metal oxide NPs, reaching the lowest value of 1.8 eV for samples doped with WO3 NPs. All optical constants were determined, and a graph of their values vs. wavelength was created. The FTIR analysis confirmed the presence of metal oxide NPs.